Essay as a Hydrofoil Boat: Reflections on Reading Jan Tomkowski’s Anthology of Polish Literary Essay - Kuczyńska-Koschany, Katarzyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The paper is a multifaceted and contextual attempt at discussing the anthology of Polish literary essay in the version proposed by Jan Tomkowski in the edition of Biblioteka Narodowa (Series I, no. 329). It is also an essay on this essay anthology.